Dualitas makna konotatif dan denotative dalam surat an-nur ayat 35 - Abdillah, Rifqy (Maliki Interdisciplinary Journal, 2025)
Surah An-Nur verse 35, known as Ayat an-Nur or the “Verse of Light,” is one of the most aesthetically profound and complex verses in the Qur’an. This verse portrays Allah as the source of light in the heavens and the earth, conveying both denotative and connotative meanings. The denotative meaning emphasizes Allah as the giver of guidance and the source of life, while the connotative meaning opens space for spiritual interpretations, including the concept of Nur Muhammad in Sufi tradition. This study employs a qualitative, literature-based approach to analyze the literal and symbolic meanings within the verse, and how these two dimensions synergize to shape a deeper understanding of divinity and guidance in Islam. The findings indicate that the interpretation of Surah An-Nur verse 35 is not merely literal, but also involves a profound reflection on divine symbols that guide humans toward higher spiritual consciousness.